AN INFLUENCE OF QUALITY, ON SYSTEM USER SATISFACTION IN INSTANCE LEVEL FINANCIAL APPLICATION SYSTEM - Ferry Safriandi; Aria Masdiana Pasaribu; Windy Aginta (SEAN Institute, 2023)
This research deals with four variables, namely system quality, service quality, information quality and user satisfaction. The aim of this research was to know whether there was an effect of system quality, service quality and information quality to SAKTI user satisfaction. The sample of this research was 83 staff at KPPN North Sumatra who used SAKTI. The research data was analyzed using Multiple Linear Regression Analysis which was calculated by SPSS 2.2. From the data analysis, it was found that the implementation of SAKTI applications has been empirically successful. Based on four proposed hypotheses, all of them are proven and accepted. The service system affected the highest value. It also showed that there was a positive effect of system quality, service quality and information quality to SAKTI user satisfaction. to sum up,